2000
DOI: 10.1161/01.cir.102.11.1221
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Troponin I and T Modification Detected in Serum From Patients With Acute Myocardial Infarction

Abstract: Background-Cardiac troponin I and T (cTnI and cTnT) are specific biochemical serum markers for acute myocardial infarction (AMI). However, cTnI diagnostic assays are plagued by difficulties, resulting in Ն20-fold differences in measured values. These discrepancies may result from the release of the numerous cTnI modification products that are present in ischemic myocardium. The resolution of these discrepancies requires an investigation of the exact forms of cTnI present in the bloodstream of patients after my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
187
2
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(198 citation statements)
references
References 24 publications
3
187
2
6
Order By: Relevance
“…Wu et al showed the presence of immunoreactive cTnT fragments in the circulation of acute myocardial infarction (AMI) patients (7). Somewhat later, in a study by Labugger et al on troponin I and T degradation in patients with AMI, Western blot data clearly showed the intact protein at 42 kDa, one major (~26 kDa) fragment and two additional minor fragments [~32 kDa] (8). In addition to their presence in serum, cTnT fragments have also been detected in healthy human heart tissue homogenates using the antibodies of the third generation cTnT immunoassay (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al showed the presence of immunoreactive cTnT fragments in the circulation of acute myocardial infarction (AMI) patients (7). Somewhat later, in a study by Labugger et al on troponin I and T degradation in patients with AMI, Western blot data clearly showed the intact protein at 42 kDa, one major (~26 kDa) fragment and two additional minor fragments [~32 kDa] (8). In addition to their presence in serum, cTnT fragments have also been detected in healthy human heart tissue homogenates using the antibodies of the third generation cTnT immunoassay (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…A direct interaction at the analytical level (9) could occur. Labugger et al showed that the sera of patients with myocardial infarction has not only intact troponin I, but also a set of modified products and phosphorylated troponin (10). ALP could be involved in dephosphorylation processes involving phosphorylated troponin, with a possible impact in troponin measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal degradation of cardiac TnI was reported in a tail suspension rat model that simulated microgravity [34]. More interestingly, several groups have reported degradation products of TnI in serum of patients after acute myocardial infarction (AMI) [35][36][37]. Degradation products of TnT were also found both in animal models of ischemia/reperfusion injury [38,39] and in serum of patients with AMI [40,41].…”
Section: Degradationmentioning
confidence: 99%
“…Protein degradation often involves significant molecular weight (MW) reduction, which can be readily detected by 1-D-gel separation followed by Western blot analysis [31,32,[34][35][36][37][38][39][40][41]. Comparative 2-DE was also used to study proteomic changes on a broader scale, and PMF can be employed to identify changed proteins [46].…”
Section: Degradationmentioning
confidence: 99%